Characterization of MiR319-Regulated TCPs in Maize Development - Novitzky, Katherine (East Carolina University)
Maize produces two inflorescences, the tassel and the ear, that are essential for reproduction. Both inflorescences arise from similar inflorescence primordia and are patterned largely by the same developmental regulators. Some of these inflorescence regulators are also responsible for leaf development and are critical for establishing plant architecture. TEOSINTE BRANCHED1/CYCLODIA/PCF1&2 (TCPs) are a unique class of plant-specific transcription factors that control proliferation and differentiation to establish plant architecture. A subset of TCPs (CIN-TCP) are regulated by microRNA (miRNA) miR319 and are required for petal and leaf development in multiple plant species. miRNAs are short non-coding RNAs that direct cleavage of target mRNAs. The maize fuzzy tassel (fzt) mutant is a hypomorphic allele of dicer-like1, which encodes a key enzyme required for miRNA biogenesis. fzt mutants have a broad range of vegetative and reproductive defects including reduced plant and leaf size, meristem indeterminacy in the inflorescences, and sex determination defects. fzt has reduced levels of some miRNAs, including miR319. Because miR319 is significantly reduced in fzt mutants and TCP genes have well-known roles in plant development, we hypothesized that mis-expression of TCP genes might contribute to the fzt phenotype. RNA-seq analysis of tassel primordia indicated that CIN-like TCPs were expressed at similar levels in fzt mutants and normal siblings. RNA-seq at the whole tissue level cannot detect subtle changes in expression domain or timing, however, so I examined the spatiotemporal expression of miR319-targeted TCPs in shoot apices and tassel primordia using RNA in situ hybridization. Preliminary data suggests that at least two TCP genes are expressed in all inflorescence meristems and floral primordia. I also initiated experiments to establish mutant lines in several TCP genes for functional analyses.
Keywords: Molecular biology; Plant sciences; Maize; microRNAs; TCP; Corn--Development; Corn--Genetics; Developmental biology; Inflorescences